ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DI KEDAI KOPI LOKAL KOTA MATARAM - Hendra Juniardi; Addinul Yakin; Tajidan Tajidan (Fakultas Pertanian Universitas Mataram, 2021)
The research aims to: (1) Analyze how much and how gender influences purchasing decisions at Coffeeshop in Mataram City; (2) Analyze how much and how ages influence on purchasing decisions at coffeeshops in Mataram City; (3) Analyzing how much and how the influence of education level on purchasing decisions at coffee shops in Mataram City; (4) Analyze how much influence the level of income on purchasing decisions at coffee shops in Mataram City; (5) Analyzing the extent and influence of store atmosphere on purchasing decisions at coffee shops in Mataram City; (6) Analyzing how much and how the influence of prices on purchasing decisions at coffee shops in Mataram City; (7) Analyzing the extent and influence of location on purchasing decisions at coffee shops in Mataram City; (8) Analyze how much influence and how the quality of the product on purchasing decisions at the coffee shops in MataramCity. The results showed that; (1) Gender (X1) does not significantly affect consumer purchasing decisions in coffee shops in the city of Mataram. (2) Ages (X2) has a positive effect on coffee purchasing decisions in coffee shops in the city of Mataram. (3) Education (X3) negatively influences coffee purchasing decisions in coffee shops in the city of Mataram. (4) Revenue (X4) has a positive effect on coffee purchasing decisions in coffee shops in the city of Mataram. (5) Store Atmosphere (X5) has a positive effect on coffee purchasing decisions in coffee shops in the city of Mataram. (6) Price (X6) has a positive effect on coffee purchasing decisions in coffee shops in the city of Mataram. (7) Location (X7) has a positive effect on coffee purchasing decisions in coffee shops in the city of Mataram. (8) Product Quality (X8) has a positive effect on coffee purchasing decisions in coffee shops in the city of Mataram.